2020
DOI: 10.1186/s13690-020-00459-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infections among health professional students in Mwanza city,Tanzania in 2016

Abstract: Background The World Health Organisation (WHO) recommends the vaccination against Hepatitis B virus in all infants and children up to the age of 18 years. In addition, adults in high-risk groups should also be vaccinated. This study investigated the prevalence and factors associated with Hepatitis B Virus (HBV) infections among health professional students in the city of Mwanza, Tanzania in order to provide data that can assist in devising prevention and control strategies in this special group. Methods A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…These results are consistent with prior research that has suggested that HBsAg is a hazard factor for the development of hepatocellular carcinoma (70,71). In the well-differentiated class, the results suggest a strong positive correlation between tumor size and the predictors (tumor size, HBsAg, HCV, and NAFL) (24,72,73). Furthermore, a unit increase in tumor size is associated with a 19.45 increase in tumor size of well-differentiated patients who test positive for HBsAg, HCV, and NAFL.…”
Section: Age and Tumor Sizesupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with prior research that has suggested that HBsAg is a hazard factor for the development of hepatocellular carcinoma (70,71). In the well-differentiated class, the results suggest a strong positive correlation between tumor size and the predictors (tumor size, HBsAg, HCV, and NAFL) (24,72,73). Furthermore, a unit increase in tumor size is associated with a 19.45 increase in tumor size of well-differentiated patients who test positive for HBsAg, HCV, and NAFL.…”
Section: Age and Tumor Sizesupporting
confidence: 91%
“…In patients with chronic liver illnesses such hepatitis B, hepatitis C, and NAFLD, AFP's low sensitivity and specificity become even more apparent. For instance, one study found only 41% sensitivity in hepatitis C patients and 29% sensitivity in non-alcoholic fatty liver disease patients (NAFLD) (22)(23)(24)(25). Since this is the case, AFP can only be used in conjunction with other markers in the diagnosis and follow-up of HCC (26).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other studies from different population groups in Tanzania which placed Tanzania in an intermediate endemicity status according to the WHO with prevalence between 2% and 8%. In comparison to other previous studies among healthcare workers (7%) and among the HIV-infected population (6.9%) [ 20 , 21 ] the reported prevalence in the current study is comparable. In comparison to previous studies in other countries that reported prevalence of 11.9% (Zambia) [22] , 19.3% (Iran) [23] , and 30.5% (Turkey) [24] the reported prevalence in the current study is low.…”
Section: Discussionsupporting
confidence: 60%
“…This cross-sectional study was conducted in Mwanza region of Tanzania among household contacts of HBV index cases from July to August 2023. This region was selected because it is among regions with a high prevalence of HBV infection varying in different populations including healthcare workers, pregnant women, children, and people living with HIV [18] , [19] , [20] , [21] .…”
Section: Methodsmentioning
confidence: 99%
“…In Mozambique, laboratory students usually start their practical education in hospitals and, in some cases, take on routine activities in the department with significant exposure but limited experience. HBV infection during the student period is supported by studies from sub-Saharan Africa that show a high prevalence of HBV among health professional students [27][28][29][30]. On the other hand, we cannot eliminate the possibility that the infection in HCWs is not occupational.…”
Section: Plos Onementioning
confidence: 86%